2021
DOI: 10.5964/jspp.7313
|View full text |Cite
|
Sign up to set email alerts
|

The meaning of respect under varying context conditions

Abstract: The concept of respect figures prominently in several theories on intergroup relations. Previous studies suggested that the experience of being respected is primarily related to the feeling of being recognized as an equal, as opposed to social recognition of needs or achievements. Those studies focused, however, on either minority groups or ad hoc groups, thereby possibly giving equality recognition an advantage. This article extends previous findings by comparing societal groups situated in various contexts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The data came from a large research project directed by the last author concerning life in pluralistic societies. To gain access to the data from this project, we asked contributors to the research project to submit the data sets from their already published (Krys et al, 2020; Paffrath & Simon, 2020; Schaefer & Simon, 2019; Simon, Eschert, et al, 2019; Simon et al, 2016, 2019; Simon & Schaefer, 2016, 2018) or not yet published articles (Schaefer et al, 2021) that included the relevant measurements for integration into our analysis. Besides measures of tolerance and approval, the data sets had to contain at least one measure of respect.…”
Section: Methodsmentioning
confidence: 99%
“…The data came from a large research project directed by the last author concerning life in pluralistic societies. To gain access to the data from this project, we asked contributors to the research project to submit the data sets from their already published (Krys et al, 2020; Paffrath & Simon, 2020; Schaefer & Simon, 2019; Simon, Eschert, et al, 2019; Simon et al, 2016, 2019; Simon & Schaefer, 2016, 2018) or not yet published articles (Schaefer et al, 2021) that included the relevant measurements for integration into our analysis. Besides measures of tolerance and approval, the data sets had to contain at least one measure of respect.…”
Section: Methodsmentioning
confidence: 99%
“…In accordance with the theory of recognition (Honneth 1994), respect can be conceptualized as equality recognition (Dillon 2018;Simon 2007). This is supported by empirical research for minorities and for majorities, although somewhat more consistently for the former than the latter (Schaefer et al 2021). According to selfcategorization theory (Turner et al 1987), shared group membership induces perceived interchangeability of ingroup members, which translates into a perceived entitlement to equal and/or respectful treatment by fellow ingroup members (Simon 2007;Wenzel 2004).…”
Section: Antecedent: Equality-based Respectmentioning
confidence: 90%
“…Huo and Binning (2008) suggested that people seek to be accorded status in interactions with authority figures, and inclusion in interactions with peers, but this hypothesis was not corroborated in later empirical investigations (Huo et al, 2010). Work in the social recognition framework by Simon et al’s has mostly focused on demonstrating a supreme role of equality in intergroup respect experiences (e.g., Reininger et al, 2020; Simon, Grabow, & Böhme, 2015), tending to neglect variations in the extent to which other forms of recognition result in feelings of respect (e.g., Simon et al, 2016; Simon, Grabow, & Böhme, 2015; but see Schaefer et al, 2021). Last, some contextualized definitions of respect have been brought forward for different professional situations (e.g., leadership: van Quaquebeke & Eckloff, 2010; nursing: Koskenniemi et al, 2015) or different relationships (between romantic partners or parent and child: Frei & Shaver, 2002).…”
Section: An Alternative: Social Worth In Interdependent Interactionsmentioning
confidence: 99%